2019
DOI: 10.2478/jolace-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Reading and Writing Skills to Young Learners in English as a Foreign Language Using Blogs: A Case Study

Abstract: This study focused on the development of reading and writing skills to a group of B1 level learners of English in a private language institute in Athens, Greece with the aid of blogs (a web tool), since Computer Assisted Language Learning (CALL) enhances foreign language learning. To this end, two groups of young learners were formed; the control group which was taught through the traditional coursebook and the experimental group which was taught through a differentiated approach to language teaching. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…A number of previous studies have concentrated on the effectiveness, effects, and benefits of blended learning using varying designs, scopes, and participants (e.g. Abdul Rahman et al, 2020;Alrouji, 2020;Annamalai, Tan, & Abdullah, 2016;Anggrawan, 2020;Camalahan & Ruley, 2014;Jin, Su, & Lei, 2020;Lam, Hew, & Chiu, 2017;Lien, 2015;McCall, 2017;Milad, 2017;Permana & Santosa, 2018;Permanda, 2017;Scott, Ulmer-Krol, & Jason, 2020;Spanou & Zafiri, 2019;Yusuf, Yusuf, Erdiana, & Pratama, 2018). These studies proved that blended learning is significantly effective in developing positive learning outcomes among ESL students.…”
Section: Blended Learning In the Esl Writing Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of previous studies have concentrated on the effectiveness, effects, and benefits of blended learning using varying designs, scopes, and participants (e.g. Abdul Rahman et al, 2020;Alrouji, 2020;Annamalai, Tan, & Abdullah, 2016;Anggrawan, 2020;Camalahan & Ruley, 2014;Jin, Su, & Lei, 2020;Lam, Hew, & Chiu, 2017;Lien, 2015;McCall, 2017;Milad, 2017;Permana & Santosa, 2018;Permanda, 2017;Scott, Ulmer-Krol, & Jason, 2020;Spanou & Zafiri, 2019;Yusuf, Yusuf, Erdiana, & Pratama, 2018). These studies proved that blended learning is significantly effective in developing positive learning outcomes among ESL students.…”
Section: Blended Learning In the Esl Writing Contextmentioning
confidence: 99%
“…In essence, previous studies found that students' writing performance had improved significantly after learning through the blended learning approach (Annamalai et al, 2016;Camalahan & Ruley, 2014;Jin et al, 2020;Lam et al, 2017;Lien, 2015;Milad, 2017;Permana & Santosa, 2018;Scott et al, 2020). Blended learning was found to improve ESL learners' writing ability, essay composition, critical arguments, linguistic competencies, grammar, spelling, topic sentence, punctuation marks, capitalization, organization, planning as well as reduce language anxiety and outline ideas (Adas & Bakir, 2013;Challob, Bakar, & Latif, 2016;Lam et al, 2017;Permana & Santosa, 2018;Spanou & Zafiri, 2019;Yusuf et al, 2018).…”
Section: Blended Learning In the Esl Writing Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…They include the following elements: personalized scaffolding to support learners in bridging the gap between learner's needs to complete the tasks; using flexible means to reach defined results by offering multiple paths to achieve set goals; "mining subject area expertise" by using various navigations; creating caring classrooms that acknowledge and value the unique learner's attributes. Spanou and Zafiri (2019) proposed the ways of applying differentiation via the implementation of information technologies.…”
Section: Literature Reviewmentioning
confidence: 99%